2006
DOI: 10.1016/j.cdp.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening among obese versus non-obese patients in primary care practices

Abstract: BACKGROUND-Obesity is associated with increased colorectal cancer incidence and mortality. Previous studies using telephone survey data showed that obese women were less likely to receive colorectal cancer screening. It is unknown if this is true among patients in primary care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 57 publications
(57 reference statements)
2
82
2
1
Order By: Relevance
“…Interaction analyses with other environmental factors revealed that, among the combinations above, ATGCGT was the one that predisposed the most to CRC, as it was the only one found to be additionally associated with a perceptible increase in the risk of CRC in obese individuals (f14.4% of the study population). This last observation is a good example of gene-environment interaction: In a way, the genetic background seems to exacerbate the procarcinogenic effect of the environmental factor, because, in our cohorts, obesity alone was not found to be associated with an increased CRC risk as reported in the literature (41). On the other hand, genetic expression seems to be influenced by environmental factors, as independent analysis of the ATGCGT combination showed no association with CRC risk.…”
Section: Discussionsupporting
confidence: 70%
“…Interaction analyses with other environmental factors revealed that, among the combinations above, ATGCGT was the one that predisposed the most to CRC, as it was the only one found to be additionally associated with a perceptible increase in the risk of CRC in obese individuals (f14.4% of the study population). This last observation is a good example of gene-environment interaction: In a way, the genetic background seems to exacerbate the procarcinogenic effect of the environmental factor, because, in our cohorts, obesity alone was not found to be associated with an increased CRC risk as reported in the literature (41). On the other hand, genetic expression seems to be influenced by environmental factors, as independent analysis of the ATGCGT combination showed no association with CRC risk.…”
Section: Discussionsupporting
confidence: 70%
“…Previous research has suggested that body image avoidance, especially for women, is related to lower quality of life (Cash et al, 2005), greater health risk, and decreased involvement in a variety of life events (Feingold & Mazzella, 1998;Ferrante, Ohman-Strickland, Hudson, Hahn, Scott, & Crabtree, 2006;Latner, 2008;Ostbye et al, 2005). Data for the current study was extracted from a largescale, internet-based survey on how size and body image predict avoidance behaviors in mainly overweight and obese, adult agerepresentative U.S. women and men of varying ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals, for example, might be less likely than non--obese persons to be screened for colorectal and breast cancer (Eichholzer et al, 2015;Ferrante et al, 2006) even though the evidence is not consistent.…”
Section: Observed In Their Cross--sectional Analysis Of Data From Thementioning
confidence: 99%